2015
DOI: 10.1186/s12966-015-0297-y
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and artificially sweetened beverage consumption and adiposity changes: National longitudinal study

Abstract: BackgroundIn response to increasing policy action and public concern about the negative health effects of sugar-sweetened beverages (SSBs), there is increased promotion of artificially sweetened beverages (ASBs). These have been linked with obesity and diabetes in recent experimental work. This study examined associations between SSB and ASB consumption and changes in adiposity in a nationally representative sample of UK children.MethodsWe conducted a longitudinal study of 13,170 children aged 7–11 years in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 29 publications
7
56
0
3
Order By: Relevance
“…In 2 studies under-reporters were included in the analysis but with adjustment for underreporting, and in 4 studies under-reporters were excluded. Five studies used BMI as body weight outcome [20,21,22,23,24], 5 BMI Z-score [25,26,27,28,29], 3 body fat [30,31,32], 3 waist circumference [33,34,35], and 1 weight-for-height z-score [36] (table 1). Almost all (94%) of the articles showed a positive association between SSB intake and body weight measures, meaning that a higher SSB consumption lead to a higher degree of adiposity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 studies under-reporters were included in the analysis but with adjustment for underreporting, and in 4 studies under-reporters were excluded. Five studies used BMI as body weight outcome [20,21,22,23,24], 5 BMI Z-score [25,26,27,28,29], 3 body fat [30,31,32], 3 waist circumference [33,34,35], and 1 weight-for-height z-score [36] (table 1). Almost all (94%) of the articles showed a positive association between SSB intake and body weight measures, meaning that a higher SSB consumption lead to a higher degree of adiposity.…”
Section: Resultsmentioning
confidence: 99%
“…This prospective cohort study included about 100 children with a mean age of 4 years and used food records with the Food Guide Pyramid as the dietary assessment method. On the contrary, the study by Laverty et al [32] also used percent body fat (by bioelectrical impedance analysis) as an outcome measure but observed a positive association with SBBs. They included approximately 13,000 children with a mean age of 9 years and used caregiver reporting as the dietary assessment method.…”
Section: Discussionmentioning
confidence: 99%
“…Another longitudinal study with over 13 000 children from the United Kingdom found that daily ASB consumption was associated with greater increase in body fat percentages, as measured by bioelectrical impedance, between ages 7 and 11 24. In another longitudinal cohort with over 500 children from the United Kingdom, ASB consumption at 5–7 years of age was associated with increased fat mass, as measured by DXA, at 9 years of age 25.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in one study, replacing sugar-sweetened beverages with artificially-sweetened soft drinks was estimated to result in lower weight gain across time, but only in those who were already overweight or obese at baseline not in normal weight subjects [25]. In contrast, a separate study in adults indicated that both weight gain and the likelihood of becoming overweight or obese were significantly higher in individuals who consumed diet soft drinks at baseline compared to those who did not [26] and a prospective study that examined children between 7 and 11 years of age indicated that daily consumption of artificially-sweetened beverages promoted both increased BMI and increased adiposity [6]. Observational work has also indicated that diet soft drink consumption is associated with increased caloric intake from other foods, including those that are energy dense, but of low nutritional quality [27,28].…”
Section: But What About Weight?mentioning
confidence: 99%
“…And increasing numbers of people appear to be choosing to consume beverages sweetened with high-intensity sweeteners. For example, in the U.S., 24% of adults and 12% children aged reported consuming such beverages, while a recent study in the UK reported approximately 39% of the 11-year-old children studied were daily consumers of artificially-sweetened soft drinks [6,7]. …”
Section: Introductionmentioning
confidence: 99%